The origin of Icelandic mtDNA lineages from haplogroup C - Sigríður Sunna Ebenesersdóttir 1982- (2010)
In this study, genetic and genealogical data were combined to make inferences about a rare mtDNA haplotype found in Iceland that belongs to haplogroup C1. While most of the Icelandic mtDNA pool originated in the British Isles or Scandinavia, this haplotype is likely to have a more distant origin, either from East Asians or Native Americans.